Letter to Jane Tolmach from Stanley Mosk - Stanley Mosk:::::: (1960)
A letter to Jane Tolmach from Stanley Mosk that discusses President John F. Kennedy's Presidential inauguration. The letter tells Jane that an official invition will be sent out to her and that she is invited to attend pre-inauguration activities.